Propoxyphene Mediates Oxyhemoglobin-Induced Injury in Rat Cortical Neurons Through Up-Regulation of Active-β-Catenin - Li, Yuqian; Wang, Jiancai; Li, Zhihong; Cheng, Hongyu; Zhang, Zhuo; Luo, Tao; Zhang, Xingye; Gao, Guodong; Lu, Huashan; Li, Lihong (Frontiers in Pharmacology, 2020)
Wnt/β-catenin signaling is engaged in various biological processes, including the development of central nervous system. The dysfunction of mitochondrial has been shown to participate in the progress of Subarachnoid hemorrhage(SAH). Traumatic subarachnoid hemorrhage(tSAH) is a serious complications in acute craniocerebral trauma. Opioids can activate the canonical Wnt/β-catenin signaling. c-Myc, a down-stream protein of Wnt/β-catenin signaling, contribute to the fusion of mitochondria. Here, we investigated the protective roles of Propoxyphene(Pro) against Oxyhemoglobin (OxyHb)-induced primary cultured neuron apoptosis. The data indicated that pro rescued active-β-catenin from the OxyHb induced decline. Furthermore, pro attenuated the OxyHb-induced apoptosis and fission of mitochondria in primary cortical neuron. However, the protective effects were abrogated under active-β-catenin-deficient conditions. Together, the data presented here showed that Pro, a weak opioid analgesic drug, attenuates the OxyHb-induced mitochondria-dependent apoptotic in an active-β-catenin-c-Myc-dependent manner.